OPTIMALISASI USAHA UMKM KRUPUK GENDAR MELALUI PENINGKATAN STRATEGI PEMASARAN - Ristiani Widia Astutik; Nelly Aulia Febriani; Shabrina Lafinaily Mazaya; Susanti Dwi Ilhami (CV. Denasya Smart Publisher, 2026)
The Kuliah Kerja Usaha (KKU) program is a form of community service carried out by university students aimed at supporting the development of Micro, Small, and Medium Enterprises (MSMEs) through the utilization of promotional media and business digitalization. This activity was conducted at the Krupuk Gendar MSME with a focus on improving business identity and expanding marketing reach. The implementation methods included observation, interviews, socialization with business owners, mentoring, and evaluation. The work programs carried out included the creation of business banners, Google Maps registration, product labels, and social media accounts for the MSME. The results showed that the business banner increased the attractiveness of the MSME’s identity, Google Maps made it easier for consumers to locate the business, product labels provided a more attractive and professional appearance, and social media accounts helped expand digital promotion. This KKU program had a positive impact on improving the branding and marketing of Krupuk Gendar Bu Harti MSME in Turusgede Village, Rembang.